Metal complexes of vanillin - and 2-furaldehyde-phenylthiosemicarbazohes - B.V. Agarwala; Mrs. Papia Chatterjee (Bulletin of the Chemical Society of Ethiopia, 1990)
Bull. Chem. Soc. Ethiop., 4(l), 39-44 (1990).